EVALUATION OF PERFORMANCE INDICATORS IN COMMERCIAL BANKS: MODERN APPROACHES AND CHALLENGES (American Journal of Business Management, Economics and Banking, 2025)
The evaluation of the performance of commercial banks is a crucial element in analyzing the financial condition and stability of credit institutions. This article explores various approaches to assessing the efficiency of banks, including both traditional methods and modern innovative tools. Particular attention is paid to key performance indicators (KPIs), such as profitability, liquidity, asset quality, and innovative approaches, including the use of digital technologies to improve analytics. Based on statistical data obtained from the financial reports of major banks, an analysis is conducted on the relationship between financial indicators and the overall performance of banking institutions. The article also provides a critical assessment of existing methods and suggests ways to improve performance evaluation practices in the face of dynamic economic changes.